PERBEDAAN HASIL BELAJAR PRAKTIKUM CETAK SARING YAN MENGGUNAKAN METODE KERJA KELOMPOK DENGAN PEMBERIAN TUGAS INDIVIDU PADA SISWA KRIYA TEKSTIL SMKN 4 PADANG - Aminur Miswah, Drs. Eswendi, M.Pd., Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2016)
The purpose of this study was to examine differences in learning outcomes practicum screen printing between ( 1 ) a method of group work by giving individual assignments in SMKN 4 Padang, ( 2 ) group work method with the conventional method in SMKN 4 Padang, ( 3 ) the provision of individual tasks with methods conventional SMKN 4 Padang. Samples were students of class XI Textile Craft SMKN 4 Padang taken by purposive sampling technique. Data collected by using the performance test. The findings of the study are ( 1 ) There are differences in learning outcomes between methods practicum Screen Printing group work by giving individual assignments at the Department of Textile Craft SMKN 4 Padang. ( 2 ) There are differences in learning outcomes between the Screen Printing lab group work method with conventional methods SMKN 4 Padang. ( 3 ) There is no difference in learning outcomes between the administration practicum Screen Printing individual tasks to conventional methods in SMKN 4 Padang.Kata kunci: metode kerja kelopok, pemberian tugas